Usulan Strategi Pemasaran Menggunakan Blue Ocean Strategy (BOS) pada Usaha Kecil Menengah Pempek Ogan Palembang - Muhammad Nur; Fitriani Surayya Lubis; Chilsy Vebiola Sandy; Ekie Gilang Permata; Silvia Silvia (LPPM ITK, 2021)
UKM Pempek Ogan is a small industry engaged in the food sector. This UKM was founded in 2007. The main problem of UKM Pempek Ogan Palembang is the slow and monotonic development and business innovation i.e. the promotion strategy implemented is not well designed to increase sales and compete with similar businesses. Consequently, the business experienced declined sales and therefore, reducing revenues if appropriate measures are not taken. The purpose of this research is to develop new strategies, marketing strategies, by creating new innovations for UKM Pempek Ogan Palembang using Blue Ocean Strategy. The Blue Ocean Strategy is a method to develop a new value innovation that is not yet owned by competitors to divert from intense competition among business actors. The BOS method has several steps in its application, namely the creation of a strategy canvas, the creation of a four-step framework i.e. eliminating, enhancing, reducing, and creating, of the creation of three characteristics of a good strategy, namely focus, divergence and motto. Our findings from the strategy canvas suggested that there are several indicators whose values ​​are below competitors. The new innovation applied to UKM Pempek Ogan Palembang as a diversion from competitors by the framework of four steps is to reduce a product price. Moreover, product variants, social media advertising, sales promotion, employee appearance, cleanliness and comfort of the place as well as poor-designed-banners should be improved. We suggested frozen pempek and pempek with unique shapes are created for new and fresh looks as a new innovation.